Analyzing the Impact of ISO 9001:2015 Implementation and Human Resource Characteristics on Employee Performance: The Role of Organizational Characteristics as an Intervening Variable at PDAM Tirtanadi, North Sumatra - Sahrim, Sahrim; Kholik, Kholilul (Lafadz Jaya Publisher, 2025)
Successful companies recognize that business improvement is fundamentally based on a system that is implemented consistently and efficiently, leading to better company performance. This system needs to be documented and written down so that employees understand the company's objectives and expectations. Consistent implementation of this system is a key principle in quality management. The implementation of the ISO 9001:2015 Quality Management System can increase employee productivity, which in turn improves the company's effectiveness and efficiency, ultimately enhancing the company's competitiveness. In the ISO 9001:2015 Quality Management System, Organizational Characteristics positively and significantly influence Performance, with an original sample value of 0.343 and a p-value of 0.001. Human Resource Characteristics have a significant impact on Organizational Characteristics, with an original sample value of 0.366 and a p-value of 0.001. Human Resource Characteristics positively and significantly affect Performance, with an original sample value of 0.265 and a p-value of 0.042. The ISO 9001:2015 Quality Management System positively and significantly influences Organizational Characteristics, with an original sample value of 0.535 and a p-value of 0.000. The ISO 9001:2015 Quality Management System positively and significantly influences Performance, with an original sample value of 0.321 and a p-value of 0.004. Human Resource Characteristics have a positive and significant effect on Performance through Organizational Characteristics, with an original sample value of 0.126 and a p-value of 0.015. The ISO 9001:2015 Quality Management System positively and significantly influences Performance through Organizational Characteristics, with an original sample value of 0.184 and a p-value of 0.005.